2015
DOI: 10.3109/08880018.2015.1057310
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin—A New Marker in Febrile Neutropenia: Comparison With CRP and Procalcitonin

Abstract: In this study, we aimed to determine serum adrenomedullin levels and compare them with levels of C-reactive protein (CRP) and procalcitonin (PCT). Cancer patients aged 0-18 years who experienced febrile neutropenia attacks were included in the study. Adrenomedullin, CRP, and PCT were analyzed at admission, day 3, and days 7-10 later. Fifty episodes of febrile neutropenia that developed in 37 patients were analyzed in this study. The mean age of the patients was 7.5 ± 4.7 (1-18) years. The patients had leukemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…ADM showed a stronger correlation as severity predictor than the other two tested biomarkers, CRP and PCT. (62) In adults, ADM has been extensively studied not only in sepsis but also in specific infections such as severe community-acquired pneumonia. (63,64) …”
Section: Introductionmentioning
confidence: 99%
“…ADM showed a stronger correlation as severity predictor than the other two tested biomarkers, CRP and PCT. (62) In adults, ADM has been extensively studied not only in sepsis but also in specific infections such as severe community-acquired pneumonia. (63,64) …”
Section: Introductionmentioning
confidence: 99%
“…PCT levels were significantly higher in the sepsis group than those in the CDI group at admission, day 3, and days 7 -10. In the sepsis group, PCT levels on days 7 -10 days were significantly higher than those in the sepsis group (4). PCT values from the deceased patients on days 7 -10 were significantly higher than those from patients who survived.…”
Section: Contextmentioning
confidence: 82%
“…First, in his study, adrenomedullin was used as a biomarker in the febrile neutropenia episodes of children with cancer. Among adrenomedullin, CRP, and PCT, procalcitonin demonstrates the highest correlation with the severity of infection (4).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies reported the applicability of ADM as a biomarker in cardiovascular diseases, including the prognosis of future cardiovascular events in high-risk patients or the clinical outcomes after acute heart failure and myocardial infarction [191][192][193]. In addition, ADM levels can be used as a risk marker for ischemic stroke, for the prediction of short-term mortality in community-acquired pneumonia and sepsis, as an indicator for ectopic pregnancy or febrile neutropenia and for the prognosis of cancer progress [189,[194][195][196][197][198].…”
Section: Cancermentioning
confidence: 99%